Trypanosoma cruzi Infection Induces Cellular Stress Response and Senescence-Like Phenotype in Murine Fibroblasts - Guimarães-Pinto, Kamila; Nascimento, Danielle Oliveira; Corrêa-Ferreira, Antonia; Morrot, Alexandre; Freire-de-Lima, Celio G.; Lopes, Marcela F.; DosReis, George A.; Filardy, Alessandra A. (Frontiers in Immunology, 2018)
Trypanosoma cruzi infects and replicates within a wide variety of immune and non-immune cells. Here, we investigated early cellular responses induced in NIH-3T3 fibroblasts upon infection with trypomastigote forms of T. cruzi. We show that fibroblasts were susceptible to T. cruzi infection and started to release trypomastigotes to the culture medium after 4 days of infection. Also, we found that T. cruzi infection reduced the number of fibroblasts in 3-day cell cultures, by altering fibroblast proliferation. Infected fibroblasts displayed distinctive phenotypic alterations, including enlarged and flattened morphology with a nuclei accumulation of senescence-associated heterochromatin foci (SAHF). In addition, infection induced an overexpression of the enzyme Senescence-Associated β-galactosidase (SA-β-gal), an activation marker of the cellular senescence program, as well as the production of cytokines and chemokines involved with the senescence-associated secretory phenotype (SASP) such as IL-6, TNF-α, IL-1β, and MCP-1. Infected fibroblasts released increased amounts of stress-associated factors nitric oxide (NO) and reactive oxygen species (ROS), and the treatment with antioxidants deferoxamine (DFO) and N-acetylcysteine (NAC) reduced ROS generation, secretion of SASP-related cytokine IL-6, SA-β-gal activity, and parasite load by infected fibroblasts. Taken together, our data suggest that T. cruzi infection triggers a rapid cellular stress response followed by induction of a senescent-like phenotype in NIH-3T3 fibroblasts, enabling them to act as reservoirs of parasites during the early stages of the Chagas disease.